Hubungan antara pemberian kompensasi, gaya kepemimpinan, dan sarana-prasarana dengan motivasi kerja karyawan cleaning service di RSUP Prof. Dr. R. D. Kandou Manado - Porotu’o, Lely I.; Porotu’o, John P.; Mandey, Lucia C. (Jurnal Biomedik : JBM, 2017)
Abstract: As one of health care organizations, a hospital comprehensively covers promotive, preventive, curative and rehabilitative services for the society, therefore, it often faces problems related to the quality of hospital services which is considered inadequate or unsatisfactory. The hospital has medical staff and non-medical staff such as employees at the finance section, cleaning service, front office, and marketing. These non-medical employees have very important responsibilities and they also manage the operational systems of the hospital. This sudy was aimed to assess the relationship between compensation, leadership style, and infrastructure with work motivation of the cleaning service employees at Prof. Dr. R. D. Kandou Hospital, Manado. This was a quantitative study with a cross sectional design conducted from December to February 2017. Respondents were all cleaning service employees as many as 125 people. Analysis of the data consisted of univariate, bivariate, and multivariate analyses using SPSS. The results showed that the significant values of the variables were as follows: compensation provision (P = 0.000), leadership style (P = 0.000), and infrastructure (P = 0.102) in relation with the work motivation of the cleaning service employees. Conclusion: There were significant relationships between the compensation and leadership style with work motivation of cleaning service employees, meanwhile infrastructure had no relationship with that work motivation.Keywords: compensation, leadership style, infrastructure, work motivationAbstrak: Rumah sakit sebagai salah satu organisasi pelayanan kesehatan yang komperhensif mencakup layanan promotif, preventif, kuratif, dan rehabilitatif bagi seluruh lapisan masyarakat, sering menghadapi permasalahan mutu pelayanan yang dianggap kurang memadai atau memuaskan. Rumah sakit memiliki tenaga medis dan non-medis yaitu antara lain karyawan yang bekerja di bagian keuangan, cleaning service, front office dan pemasaran. Tenaga non-medis juga memiliki tanggung jawab yang sangat penting dalam mengelola sistem operasional rumah sakit. Penelitian ini bertujuan untuk mengetahui hubungan antara pemberian kompensasi, gaya kepemimpinan, dan sarana-prasarana dengan motivasi kerja karyawan cleaning service di RSUP Prof. Dr. R. D. Kandou. Jenis penelitian ini ialah kuantitatif dengan desain potong lintang yang dilaksanakan pada bulan Desember-Februari 2017. Respoden ialah seluruh karyawan cleaning service sebanyak 125 orang. Analisis data terdiri dari univariat, bivariat, dan multivariat dengan menggunakan SPSS. Hasil penelitian menunjukkan bahwa nilai signifikansi pemberian kompensasi (0,000), gaya kepemimpinan (0,000), dan sarana-prasarana (0,102) terhadap motivasi kerja karyawan cleaning service. Simpulan: Terdapat hubungan antara pemberian kompensasi dan gaya kepemimpinan dengan motivasi kerja karyawan cleaning service di RSUP Prof. Dr. R. D. Kandou Manado, sedangkan sarana-prasarana tidak berhubungan dengan motivasi kerja tersebut. Kata kunci: kompensasi, gaya kepemimpinan, sarana-prasarana, motivasi kerja